Sitting Face-To-Face Awake Intubation as an Alternative to a Difficult Airway: A Case Report - Dall"Aqua, Camila Gomes; Nascimento, David Ribeiro do; Japolino, Katharina Lanza; Delgado, Marina Ayres (Brazilian Journal of Case Reports, 2025)
Awake tracheal intubation is an essential skill for anesthesiologists, particularly in trauma cases where standard positioning is not feasible. While the supine sniffing position is commonly employed, the seated approach remains underutilized and lacks standardization despite its advantages. We report the case of a 24-year-old male with a screwdriver lodged in his thoracic spine who was unable to lie down and required urgent surgical intervention. Awake fiberoptic intubation was successfully performed in the seated, face-to-face position using remifentanil delivered via target-controlled infusion. Contingency plans were established, including readiness for emergent surgical airway access and availability of a second anesthesiologist. The technique enabled safe airway management without compromising spinal stability. General anesthesia was then induced without complications, and the procedure and recovery were uneventful. The patient was discharged without sequelae. This case highlights the practical advantages of awake seated intubation, including improved secretion drainage by gravity and facilitated bronchoscope navigation with minimal manipulation. Familiarity with and training in this technique can enhance patient safety and broaden the anesthesiologist’s airway management strategies in complex scenarios.